STRATEGI KEBERLANJUTAN PENGELOLAAN HUTAN MANGROVE DI TAHURA NGURAH RAI BALI - Mega Lugina; Iis Alviya; Indartik Indartik; Mirna Aulia Pribadi (Jurnal Analisis Kebijakan Kehutanan, 2017)
Pressures from various interests towards Ngurah Rai Grand Forest Park have potential to trigger of damage on mangrove ecosystem. The study aims to identify the utilization of mangroves at Ngurah Rai Grand Forest Park by local communities; to identify internal and external factors of mangrove management; and to determine mangrove management strategies. Based on SWOT analysis, the two highest internal factors which become the strengths in mangrove management are the strategic location and the largest proportion of mangrove ecosystem in Bali. While, the internal factors that become the weaknesses are the existence of garbage, mud and the sedimentation in downstream area. External factors that become opportunities for mangrove management are among others, increasing number of tourists and the location that close to other tourist destination. The threats to its managementiclude the interest of certain parties which tend to reduce the existence and sustainability of mangrove forests and waste disposal from upstream areas. Five mangrove management strategies that should be implemented, namely: implementation and enforcement of clear rules; waste management and pollution control; raising awareness and education to local communities on the importance of environment; strategic development planning considering carrying capacity; tourism development that involves the community and local wisdom.